Power and variety-seeking: A compensatory perspective - Wang, Jin; Jin, Fei (Frontiers in Psychology, 2022)
In the current research, we show that low-power state promotes variety-seeking. We argue that this effect occurs because consumers in low-power state desire control and variety-seeking as a way to restore sense of control. The effect of power on variety-seeking is reduced when consumer knowledge in a certain consumption domain is high (vs. low) because knowledge is an alternative way to retain sense of control. Three experiments provide systematic evidence for this effect across different product categories. These findings contribute to the literature on how variety-seeking can be used as a way to compensate and enhance our understanding of power and consumer knowledge.